EFFECT OF CHRONIC TREATMENT WITH A CYCLOOXYGENASE INHIBITOR ON REPRODUCTIVE PARAMETERS IN MALE RAT - Saeed, Sheikh A.; Anwar, Naheed; Khan, Khalid M.; Sarfraz, Noorjehan (Journal of Ayub Medical College Abbottabad, 2009)
Background: Indomethacin is a member of non-steroidal anti-inflammatory drugs (NSAIDs) commonly used for treatment of gout, arthritis, and other inflammatory conditions. It has been shown to inhibit ovarian prostaglandins synthesis in mammals, birds, fish and reptiles. However, the effects of its chronic administration on male reproductive functions remain largely unknown. Using rat as a model, we studied the effect of chronic treatment with indomethacin on the male reproductive system. Methods: Testosterone was measured in the serum, testicular tissue, and testicular interstitial fluid by radioimmunoassay. Moreover, we also studied the direct effect of indomethacin in vitro on luteinizing hormone stimulated testosterone secretion from the Leydig cells isolated from various treatment groups. Results: Indomethacin treatment for 50 days caused a significant but reversible decrease in prostate weight, epididymal sperm reserves and sperm motility score compared with control rats (p<0.05). In vitro stimulation of Leydig cells isolated from treated rat’s testes with luteinizing hormone (250 µIU) produced significantly reduced testosterone compared with cells from control groups (p<0.05). Furthermore, stimulatory effect of luteinizing hormone on the control Leydig cells was significantly reduced when these cells were challenged with luteinizing hormone in the presence of indomethacin, (p<0.05). Testosterone concentration in the testicular tissue and testicular interstitial fluid reduced after indomethacin treatment (p<0.05). Conclusion: Due to its significant inhibition of key reproductive hormones, indomethacin effectively inhibits reproductive functions if used on a long-term basis. In his study, we have identified potential risks in the long-term use of cyclooxygenase inhibitors. Keywords: Cyclooxygenase inhibitor, reproductive functions, male rats